The Ergonomics Body Posture On Repetitive And Heavy Lifting Activities Of Workers In Aerospace Manufacturing Warehouse - Kamat, Seri Rahayu; Md Zula, Nur Emelia Natasha; Rayme, Nur Syafiqah; Shamsuddin, Syamimi; Husain, K. (Institute Of Physics (IOP) Publishing, 2017)
Warehouse is an important entity in manufacturing organizations. It usually involves working activities that relate ergonomics risk factors including repetitive and heavy lifting activities. Aerospace manufacturing workers are prone of having musculoskeletal disorder (MSD) problems because of the manual handling activities. From the questionnaires is states that the workers may have experience discomforts experience during manual handling work. Thus, the objectives of this study are; to investigate the body posture and analyze the level of discomfort for body posture of the workers while performing the repetitive and heavy lifting activities that cause MSD problems and to suggest proper body posture and alternatives to reduce the MSD related problems. Methodology of this study involves interviews, questionnaires distribution, anthropometry measurements, RULA (Right Upper Limb Assessment) assessment sheet and CATIA V5 RULA analysis, NIOSH lifting index (LI) and recommended weight limit (RWL). Ten workers are selected for pilot study and as for anthropometry measurement all workers in the warehouse department were involved. From the first pilot study, the RULA assessment score in CATIA V5 shows the highest score which is 7 for all postures and results after improvement of working posture is very low hence, detecting weight of the material handling is not in recommendation. To reduce the risk of MSD through the improvisation of working posture, the weight limit is also calculated in order to have a RWL for each worker. Therefore, proposing a guideline for the aerospace workers involved with repetitive movement and excessive lifting will help in reducing the risk of getting MSD.